UPAYA KELOMPOK ARUS PELANGI DALAM MEMPERJUANGKAN PENGAKUAN STATUS LGBT DI INDONESIA PADA TAHUN 2018 - 2020 - Fathan Haikal Mardiananto, (2023)
Discrimination that's been happening on sexual orientation is an actual issue in international world nowadays. A henomenon that being oppressed by countries that have a conservative view and being labeled as an omen in countries that have a strong influences in culture and religion beliefs. They going on a war between their identity and belief while there's a movement that support their sexual orientation that's been called LGBT ( Lesbian, Gay, Bisexual, Transgender) where every human that have that belief is given a freedom to choose what they want in their sexual orientation, they don't have to follow what their culture and religion on their country follows and belief, including in Indonesia. That sparks a social movement that have a base on political identity and have a joint venture with international social movement. Arus Pelangi comes as network that are working with international ovement on LGBT issues and are fighting on their rights with dvocation on persecutions that they've been through, and slowly they're seeing the light to what they will become as a LGBT group in Indonesia